2019
DOI: 10.1002/ece3.5749
|View full text |Cite
|
Sign up to set email alerts
|

Competition and succession among coral endosymbionts

Abstract: Host species often support a genetically diverse guild of symbionts, the identity and performance of which can determine holobiont fitness under particular environmental conditions. These symbiont communities are structured by a complex set of potential interactions, both positive and negative, between the host and symbionts and among symbionts. In reef‐building corals, stable associations with specific symbiont species are common, and we hypothesize that this is partly due to ecological mechanisms, such as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 85 publications
0
40
0
Order By: Relevance
“…While previous work has established that some coral species with multi-partner symbioses can expand their thermal tolerance by "shuffling" their symbionts to change the dominant symbiont genus (Baker 2003;Silverstein et al 2014;, neither the multi-year bleaching events in 2014 and 2015 (Bahr et al 2017) nor the temperature treatments and natural thermal stress event in this study appeared to induce symbiont shuffling in M. capitata. Mixed-community colonies maintained Durusdinium-dominated symbiont communities four years post-bleaching despite the potential for a competitive advantage of Cladocopium under ambient conditions (McIlroy et al 2019). Similarly, different M. capitata genotypes with mixed communities of algal symbionts had remarkably similar Cladocopium to Durusdinium ratios.…”
Section: Variation In Symbiont Community Compositionmentioning
confidence: 94%
See 1 more Smart Citation
“…While previous work has established that some coral species with multi-partner symbioses can expand their thermal tolerance by "shuffling" their symbionts to change the dominant symbiont genus (Baker 2003;Silverstein et al 2014;, neither the multi-year bleaching events in 2014 and 2015 (Bahr et al 2017) nor the temperature treatments and natural thermal stress event in this study appeared to induce symbiont shuffling in M. capitata. Mixed-community colonies maintained Durusdinium-dominated symbiont communities four years post-bleaching despite the potential for a competitive advantage of Cladocopium under ambient conditions (McIlroy et al 2019). Similarly, different M. capitata genotypes with mixed communities of algal symbionts had remarkably similar Cladocopium to Durusdinium ratios.…”
Section: Variation In Symbiont Community Compositionmentioning
confidence: 94%
“…The trends in the loss of Cladocopium from mixed-community corals may indicate some competitive advantage of Durusdinium. Previous studies have found that Durusdinium is able to outcompete Cladocopium only in thermally stressful conditions (McIlroy et al 2019), or when tradeoffs regarding growth (Jones and Berkelmans 2010;, nutrient acquisition (Baker et al 2013), and photochemical efficiency (Cantin et al 2009) diminish. Thus, the conditions of thermal stress during the mild natural warming event may have been enough to promote the preferred persistence of Durusdinium in mixed symbiont communities, but still mild enough for Cladocopium to perform relatively well in corals with no competition with Durusdinium.…”
Section: Variation In Symbiont Community Compositionmentioning
confidence: 98%
“…However, this symbiont diversity may come at a cost if competitive or antagonistic interactions occur among symbiont types. Symbiont competition, which was recently documented by McIlroy et al (2019), is one potential mechanism through which destabilizing complementarity effects could have reduced symbiont benefit to worst performing hosts in this study (Miller, 2007;Moeller & Peay, 2016;Poland & Coffroth, 2019;Stanton, 2003 An alternative interpretation of the more uniform Symbiodiniaceae communities in best performing genets is that these hosts were more successful at maintaining normal physiological function under changing conditions, which could minimize stress responses by symbionts and subsequent host immune feedbacks against symbionts (e.g., Palmer, 2018). Various components of the host immune system could also contribute to the maintenance of specific symbionts in hospite (e.g., Ratzka, Gross, & Feldhaar, 2012).…”
Section: Metrics Of Symbiont Diversity Are Higher In Hosts With Lowmentioning
confidence: 94%
“…Thus, rather than outcompeting C. goreaui in any scenario, it is more likely that D. trenchii is the "last man standing" as it is able to tolerate and then repopulate coral tissues under conditions unsuitable for other symbionts. In other words, this species seems well suited to proliferate only in the absence of other strains, e.g., under extreme environmental conditions [35], following bleaching [18], and in newly available host habitat [44]. Indeed, during the initial colonization of coral recruits D. trenchii often remained at lower than expected densities when other symbionts were present despite being able to fully colonize corals in their absence [44].…”
Section: Implications For Symbiosismentioning
confidence: 99%